Urinary Tract Endometriosis: A Review of Literature - Ralph Saadeh; Elie Finianos; Houssein El Hajj (Clinical and Experimental Obstetrics & Gynecology)
Objective: Deep endometriosis (DE) is the most severe form of endometriosis. Bowel and urinary tract are the most common sites of intrapelvic DE. Urinary tract endometriosis (UTE) mainly involves the bladder and the ureters. The two mostly accepted theories explaining the pathophysiology of UTE are the “Retrograde Menstruation Theory” and the “Müllerian Remnants Theory”. The purpose of this paper is to provide a review of literature on the UTE, a rare form, affecting only 1–6% of patients with endometriosis. Mechanism: A literature review was conducted using keywords specific to UTE and DE to identify peer-reviewed, original research articles published between 1996 and 2024. Findings in Brief: When the bladder is involved, the patient presents lower urinary tract symptoms. Ureteral endometriosis is usually asymptomatic, thus delaying early diagnosis and efficient treatment leading to cases of chronic ureteral stricture. Clinical history and examination as well as questionnaires play an important role in guiding the clinician. Diagnostic modalities include conventional imaging such as ultrasonography and magnetic resonance imaging (MRI) as well as invasive techniques such as cystoscopy. As for all endometriotic lesions, definitive diagnosis should be confirmed by histopathology. Treatment modalities include medical hormonal treatments or surgical treatment. There are a multitude of surgical techniques that are more or less invasive depending on the location and the extent of the lesion. Conclusions: UTE, is an underdiagnosed form of endometriosis, and specialists should be aware of this important entity, due to the serious health implications for women.